Expression and Application of Wu Region Cultural Elements in Suzhou Rail Transit Public Space - WANG Yuming; SUN Yuanyuan (Chengshi guidao jiaotong yanjiu, 2024)
Objective With urban regional cultural inheritance as the background, the expression and application of Wu Region cultural elements in the public space of Suzhou metro are discussed, and the application value and strategies are summarized. Method Based on the connotation of Wu Region culture, such as inclusiveness, worship of literature and education, flexibility and talent, the extraction method of Wu Region cultural elements is put forward through three ways: typical extraction, abstraction rule and cultural symbol reconstruction. The case analysis is used to analyze the application of Wu Region cultural elements in Suzhou Metro entrances and exits, public art within station and inside carriage compartment from the aspects of design description, material technology, construction technology and technical requirements. The concrete ways of constructing the unique cultural landscape of Suzhou metro with architectural elements, garden elements, cultural character, catering culture, religious beliefs, language culture, opera culture and other aspects of Wu Region culture are introduced in detail. Result & Conclusion Based on the rules of Wu Region cultural elements extraction, to realize the translation and transmission of traditional culture in Suzhou Metro public space by way of establishing Wu Region cultural symbol design system, endowing Wu Region cultural symbol functions and cultural semantics, and applying modern design means will promote significance for inheriting the urban context, shaping the urban spirit in the new era, and enhancing the soft power of urban culture.